Evaluation of the Clinical Picture and Effectiveness of Antifungal Therapy in Tinea Corporis Cases in Tropical Areas: Literature Review - Anniza Putri Abduh; Dian Amelia Abdi; Solehca Setiawati (Journal of Community Health Provision, 2026)
Tinea corporis is a superficial dermatophyte infection of the skin commonly found in tropical regions due to hot and humid environmental conditions. This disease is characterized by well-defined, scaly, annular lesions accompanied by pruritus, and is influenced by various risk factors such as age, gender, personal hygiene, and comorbidities. Various topical and systemic antifungal therapies have been used in the treatment of tinea corporis, but their effectiveness can vary depending on the clinical presentation and patient characteristics. This study is a literature review conducted by reviewing research articles related to the clinical presentation and effectiveness of antifungal therapy in cases of tinea corporis in tropical regions. The literature search was conducted through Google Scholar, PubMed, ResearchGate, Elsevier, and NCBI databases. A total of 10 articles published between 2021 and 2025 that met the inclusion criteria were analyzed descriptively and synthesized narratively. The review indicates that Trichophyton rubrum is the most common cause of tinea corporis. Topical antifungal therapy is effective in mild to moderate cases, while systemic therapies such as itraconazole, terbinafine, and griseofulvin are more effective in extensive, chronic, or resistant cases. The combination of topical and systemic therapy shows a higher cure rate and reduces recurrence rates. The clinical presentation and response to therapy for tinea corporis in tropical regions are influenced by environmental factors, patient characteristics, and the choice of antifungal regimen. Appropriate clinical evaluation and rational use of antifungal therapy, both topical and systemic, are crucial for achieving optimal cure and preventing recurrence.